PERBANDINGAN KADAR KALIUM BISULFAT (K2SO4) PADA KENTANG BEKU OLAHAN BERMEREK DAN TIDAK BERMEREK - Kartikorini, Nastiti (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST)
PERBANDINGAN KADAR KALIUM BISULFAT (K2SO4) PADA KENTANG BEKU OLAHAN BERMEREK DAN TIDAK BERMEREK Ir. Nastiti  Kartikorini, M.Kes.Prodi D3 Analis Kesehatan UM Surabaya AbstractFrozen potato is one of the processed potato prefer the physical quality of appearance, crispness and color. So it is necessary to increase the quality of frozen potatoes, especially related to shelf-life durability. Potassium bisulfate is an added food ingredient used as a preservative in frozen potatoes. Therefore, researchers wanted to conduct research to compare the levels of potassium bisulfate in processed frozen potato branded and unbranded. This research is analytic obsefasional, where this study aims to compare the levels of Kalim bisulfate in processed frozen potato branded and unbranded. As materials research, the researchers took samples of processed frozen potatoes, amounting to 6 samples branded and unbranded, amounting to 10 samples tested at the Research Institute and Consulting Industry Surabaya, East Java. Based on the results of research and data analysis, the statistical test with SPSS method. From normality test and then do different test-free t test. From the research results, obtained an average grade Potassium bisulfate (K2SO4) on branded processed frozen potatoes was 465.5 mg / kg, whereas the processed frozen potato unbranded was 569.9 mg / kg. After the test data is performed, it is known that the t value of 1.964 with sig. (P) = 0.074 which is greater than 0.05 then there is no difference in the levels of potassium bisulfate (K2SO4) on frozen potato branded and unbranded (HO accepted). From the results of research and discussion is done, it can be concluded that the results of research that has been done there is no significant comparison between the levels of potassium bisulfate (K2SO4) in processed potato branded and unbranded, where all the results of this study the positive (+) containing potassium bisulfate (K2SO4).Keyword : Frozen potato,   Potassium bisulfate